Algebra

How to solve by substitution: 8x - 4y = 16
y = 2x - 4

  1. 👍
  2. 👎
  3. 👁
  1. simplyfied

    8x - 4y = 16
    -2x + y = - 4

    1. 👍
    2. 👎

Respond to this Question

First Name

Your Response

Similar Questions

  1. How do I do this.?(Math.)

    Use the Substitution method to solve the system of equations. y - 2x = -5 3y - x = 5 Solve one of the equations for x or y. Let's solve the first one for y: y - 2x = -5 y = 2x - 5 Now let's substitute 2x - 5 for y in the second

  2. Algebra PLEASE HELP!!

    What advantages does the method of substitution have over graphing for solving systems of equations? Choose the correct answer below. A. Graphing cannot be used to solve dependent or inconsistent systems due to the nature of the

  3. math

    What is the first step in solving the linear system {2x − 3y = 11 {−x + 5y = −9 by the substitution method in the most efficient way? A. Solve the first equation for x. B. Solve the first equation for y. C. Solve the second

  4. math

    What is the first step in solving the linear system {2x−3y=11 {−x+5y=−9 by the substitution method in the most efficient way? A. Solve the first equation for x. B. Solve the first equation for y. C. Solve the second equation

  1. Help please math

    Solve using substitution. y = x – 2 x + y = 10 7x + 2y = - 8 8y = 4x Solve using elimination. 2x + 3y = 12 2x – y = 4 5x – 2y = - 19 2x + 3y = 0

  2. math

    solve using substitution: 4x+9y=24 y=1/3x+2

  3. Algebra

    Solve using substitution 5x-2y= 0 and 3x=y =-1

  4. Algebra 2

    Solve by Substitution x + 2y + z = 14 y = z + 1 x = -3z + 6

  1. Algebra

    Solve the system of equations using substitution. x + 4y = -5 3x - 8y = 45 When I tried to solve it, I got x=-17 and y=-3. When I plugged these into the first equation, it didn't work out at all. Could someone please show me the

  2. Substitution Method-Plz help

    Use the Substitution method to solve the system of equations. x + y = -4 x - y = 2 solve for x in the second equation. x= y+2 Put that in for x in the first equation: x+y=-4 (y+2) + y = -4 solve for y. Then, x= y+2 i don't get

  3. math

    solve using substitution 4x + 3y= -3 2x + y = -1

  4. math

    solve by using substitution: x=y+7 y-8=2x

You can view more similar questions or ask a new question.